Receipt of mastectomy and adjuvant radiotherapy following breast conserving surgery (BCS) in New Zealand women with BCS-eligible breast cancer, 2010–2015: an observational study focusing on ethnic differences - Karen Bartholomew; Mazin Ghafel; Sandar Tin Tin; Phyu S Aye; J Mark Elwood; Claire Hardie; Nina Scott; Jacquie Kidd; Reena Ramsaroop; Ian Campbell (BMC Cancer, 2023)
Abstract Background Women with early breast cancer who meet guideline-based criteria should be offered breast conserving surgery (BCS) with adjuvant radiotherapy as an alternative to mastectomy. New Zealand (NZ) has documented ethnic disparities in screening access and in breast cancer treatment pathways. This study aimed to determine whether, among BCS-eligible women, rates of receipt of mastectomy or radiotherapy differed by ethnicity and other factors. Methods The study assessed management of women with early breast cancer (ductal carcinoma in situ [DCIS] and invasive stages I-IIIA) registered between 2010 and 2015, extracted from the recently consolidated New Zealand Breast Cancer Registry (now Te Rēhita Mate Ūtaetae NZBCF National Breast Cancer Register). Specific criteria were applied to determine women eligible for BCS. Uni- and multivariable analyses were undertaken to examine differences by demographic and clinicopathological factors with a primary focus on ethnicity (Māori, Pacific, Asian, and Other; the latter is defined as NZ European, Other European, and Middle Eastern Latin American and African). Results Overall 22.2% of 5520 BCS-eligible women were treated with mastectomy, and 91.1% of 3807 women who undertook BCS received adjuvant radiotherapy (93.5% for invasive cancer, and 78.3% for DCIS). Asian ethnicity was associated with a higher mastectomy rate in the invasive cancer group (OR 2.18; 95%CI 1.72–2.75), compared to Other ethnicity, along with older age, symptomatic diagnosis, advanced stage, larger tumour, HER2-positive, and hormone receptor-negative groups. Pacific ethnicity was associated with a lower adjuvant radiotherapy rate, compared to Other ethnicity, in both invasive and DCIS groups, along with older age, symptomatic diagnosis, and lower grade tumour in the invasive group. Both mastectomy and adjuvant radiotherapy rates decreased over time. For those who did not receive radiotherapy, non-referral by a clinician was the most common documented reason (8%), followed by patient decline after being referred (5%). Conclusion Rates of radiotherapy use are high by international standards. Further research is required to understand differences by ethnicity in both rates of mastectomy and lower rates of radiotherapy after BCS for Pacific women, and the reasons for non-referral by clinicians.